Driver Perception toward Road Traffic Accidents in Babylon City - Amean A. Yasir (Journal of Global Pharma Technology, 2017)
Babylon has one of the highest road traffic accident (RTA) related fatality rates in Iraq. Yet, still little is known about the factors contributing to the high number of RTAs .For the first objective, identification of the main human factors that contribute to the occurrence of RTAs in Babylon, the study on human factors conducted by Gründl (2005) was replicated. The results revealed three human factors that significantly increase the risk of causing an RTA in Babylon. These factors are according to the strength of their impact: namely the human (inappropriate speed, fatigue and having a conversation with the passenger), the vehicle and the road environment. Objective this study aimed to identify the main human factors that contribute to the occurrence of RTAs in Babylon and to investigate the human road interaction as a contributing factor to the occurrence of RTAs in Babylon.Keywords: RTAs, Human, Inappropriate speed, Fatigue, Having a conversation with the passenger, the vehicle and the road environment.